2018
DOI: 10.1007/s11892-018-0993-5
|View full text |Cite
|
Sign up to set email alerts
|

Underutilized and Under Threat: Environmental Policy as a Tool to Address Diabetes Risk

Abstract: Evidence suggests that disproportionate exposures to EDCs may contribute to subgroup-specific diabetes risk; however, no federal policies regulate EDCs linked to diabetes based upon diabetogenic potential. Nevertheless, analyses of European Union data indicate that such regulation could reduce diabetes-associated costs and disease burden. Federal laws only regulate EDCs indirectly. The accumulating evidence linking these chemicals with diabetes risk should encourage policymakers to adopt stricter environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Behavioral modification informed by knowledge of obesogenic chemicals and the sources of exposures, as well as individual efforts to minimize engagement can reduce their obesogen levels. Short-term intervention studies showed that lowering known sources of common obesogen successfully reduced levels of BPA, phthalates, parabens, and triclosan [683,684]. Individual reduction of obesogen levels is predicated on knowledge of the sources of that exposure and an absence of unexpected exposures arising from contamination [685].…”
Section: Intervention and Prevention Strategiesmentioning
confidence: 99%
“…Behavioral modification informed by knowledge of obesogenic chemicals and the sources of exposures, as well as individual efforts to minimize engagement can reduce their obesogen levels. Short-term intervention studies showed that lowering known sources of common obesogen successfully reduced levels of BPA, phthalates, parabens, and triclosan [683,684]. Individual reduction of obesogen levels is predicated on knowledge of the sources of that exposure and an absence of unexpected exposures arising from contamination [685].…”
Section: Intervention and Prevention Strategiesmentioning
confidence: 99%
“…In the end, however, any effective strategy must include comprehensive and sustained efforts to reduce exposures wherever and whenever possible. Current federal environmental policies do not account for metabolic disease risk, as recently discussed for diabetes (170). Incorporating metabolic health as a relevant outcome in local, regional, national, and international policy has the potential to transform risk assessment to support legislation that is likely to reduce exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Some EDCs used in plastic production, like phthalates and bisphenol A, are even incorporated into medications, medical equipment, and medical products [80]. Little has been done to understand and eliminate EDC exposures in medical care [80] and the environment in general [81]. To bridge the gaps between knowledge and action, Dr Sargis recommended the following courses of action: (1) screening and regulating chemicals based on their metabolism-disrupting effects; (2) understanding the impact of chemical mixtures on metabolic health; (3) evaluating the combined impacts of EDCs and traditional metabolic disease risk factors or underlying illnesses; (4) evaluating the toll of EDCs in the context of other social/structural determinants of health; (5) identifying and targeting sensitive windows of development for EDC-induced diabetes; (6) understanding how EDCs interact with climate change to threaten metabolic health; (7) evaluating interventions to reduce EDC levels and/or impact; and (8) testing and implementing public policies that reduce EDC exposures [82][83][84][85].…”
Section: Environmental/community Sources Of Stressmentioning
confidence: 99%